Karakteristik Mutu Pikel Jahe dengan Penambahan Ekstrak Bawang Dayak - Anggarkasih, Made Gayatri; Fatimah, Ai Imas Faidoh; Hapsari, Rianti Dyah; Nurwitri, CC; Qalbi, Rainatul (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Processing ginger into pickles can provide added economic value and potentially become an export commodity. Ginger pickles are made by soaking ginger slices in a salt solution. Improving the quality of elephant ginger pickles can be done by adding natural dyes to have a pink color like Gari. Dayak onion extract can be used as a natural dye. This research aimed to determine the quality characteristics of ginger pickle with the addition of Dayak onion extract to the soaking medium at 7 dan 14 fermentation days and compare it with a salt solution soaking medium of various concentrations. This study is experimental research that used a Completely Randomized Design consisting of 6 treatments, namely a water-based and a Dayak onion extract-based soaking solution, each made with 5%, 7%, and 9% (w/v) salt concentration. The results showed (1) Adding Dayak Onion extract and variations of salt concentration in elephant ginger pickles had a significant effect on pH, and TPT and had no significant effect on the color and number of lactic acid bacteria); (2) Ginger pickles with a water-based 7% concentration salt solution (P2) most preferred treatment by the panelists.